ISLAMISASI BANJARMASIN (ABAD XV-XIX) - Yusliani Noor (JURNAL SOCIUS, 2013)
15th Century marked by Islamization in Banjarmasin. Banjarmasin that previously inhabited by Dayak communities; Biaju or Ngaju, Maanyan, Lawangan, Bukit and Melayu,also elite’s Hindu-Buddha who came from Java or Sumatra. Then accepted the arrival and spread of Islam through the line of trade, marriage, government bureaucracy, tasawuf and tarekat, education and the arts. The line received via the network Bubuhan, Authority, and Interest. The third network was socially connect with each other to form arelegious transformation of the old religion Kaharingan, Balian, and Hindu-Buddha to the religion of Islam.Indeginous communities through the local intelligence in transformative intermingled while receiving and applaying the teachings of Islam which was certainly supported by the bureaucracy, government, forming acommunity of Islam that Islamic Banjarish.Key words: Islamization, Community, Social Networ